Studi Komparatif Efektivitas Mckenzie Exercises dan William Flexion Exercises pada Myogenic Low Back Pain: Comparative Study of Effectiveness of Mckenzie Exercises and William Flexion Exercises in Myogenic Low Back Pain - Wahyuni Dwi Cahya; Arisandy Achmad; Sulfandi Sulfandi; Kasim Nurhas Jaiddin; Fanny Metungku (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
McKenzie and William Flexion exercises are physiotherapeutic interventions for LBPM (Low Back Myogenic Pain) to reduce pain and improve functional activity. This study aims to compare the effectiveness of the McKenzie Exercise and the William Flexion Exercises in the case of LBPM. The total sample in this study was 15 samples in group I (McKenzie Exercise) and 15 in group II (William Flexion Exercise). The measurements are VAS (Visual Analog Scale) and ODI (Oswestry Disability Index). The test results of the Mann-Whitney hypothesis on weeks 1, 2, and week three obtained p > 0,05, meaning there was no significant difference between the effectiveness of McKenzie Exercise and William Flexion Exercises against LBPM pain. While measurements of functional activity at weeks 1, 2, and week three obtained p < 0,02, which means there is a meaningful difference with the interpretation that McKenzie Exercise is more effective than William Flexion Exercises on the improvement of LBPM functional activity, The study concluded that there was no meaningful difference between the effectiveness of McKenzie Exercises and William Flexion Exercises in reducing LBPM pain. However, McKenzie's exercises are more effective than William's Flexion Exercises in improving LBPM functional activity. Keywords: LBP Myogenic, Mckenzie Exercise, William Flexion Exercise, VAS, ODI Abstrak McKenzie Exercise dan William Flexion Exercise merupakan intervensi fisioterapi pada kasus LBPM (Low Back Pain Myogenic) untuk menurunkan nyeri dan meningkatkan aktivitas fungsional. Penelitian ini bertujuan untuk membandingkan efektivitas antara McKenzie Exercise dan William Flexion Exercise pada kasus LBPM. Jumlah sampel dalam penelitian ini adalah 15 sampel pada kelompok I (McKenzie Exercise) dan 15 sampel pada kelompok II (William Flexion Exercise). Alat ukur penelitian adalah VAS (Visual Analog Scale) dan ODI (Oswestry Disability Index). Hasil uji hipotesis Mann Whitney pada pengukuran minggu 1, minggu 2, dan minggu 3 didapatkan nilai p>0,05 yang berarti tidak ada perbedaan bermakna antara efektivitas McKenzie Exercise dan William Flexion Exercise terhadap nyeri LBPM. Sedangkan pengukuran aktivitas fungsional pada minggu 1, minggu dan minggu 3 didapatkan nilai p<0,02 yang berarti terdapat perbedaan bermakna dengan interpretasi Mckenzie Exercise lebih efektif dibandingkan William Flexion Exercise terhadap peningkatan aktivitas fungsional LBPM. Kesimpulan penelitian ini adalah tidak ada perbedaan bermakna antara efektivitas McKenzie Exercise dan William Flexion Exercise terhadap penurunan nyeri LBPM. Namun McKenzie Exercise lebih efektif dibandingkan William Flexion Exercise terhadap peningkatan aktivitas fungsional LBPM. Kata Kunci: LBP Myogenic, Mckenzie Exercise, William Flexion Exercise, VAS, ODI